Space and Habitat Utilization of the Red King Crab (Paralithodes camtschaticus) in a Newly Invaded Fjord in Northern Norway - Aune, Magnus; Jensen, Jenny L. A.; Siikavuopio, Sten I.; Christensen, Guttorm N.; Nilsen, Kåre Tormod; Merkel, Benjamin; Renaud, Paul E. (Frontiers in Marine Science, 2022)
The red king crab (RCK, Paralithodes camtschaticus) was introduced to the southern Barents Sea in the 1960's with the aim to develop a new, commercially attractive stock of the species. In the subsequent decades, the stock has indeed become abundant and widespread, but the species' presence also implies intense predation on benthic biota and thereby severe degradation of benthic ecosystems. Our capacity to monitor and harvest the species efficiently is therefore imperative. Yet, fishermen report highly variable catches despite little variation in the timing and location of fishing, possibly induced by the species' migratory behaviour, which makes the search for crab aggregations time consuming and expensive. Here, we applied telemetry to investigate the migratory behaviour and habitat utilization of the RKC in a fjord in northern Norway from late May until early November. Many crabs left the study area early during the study period, but a relatively high proportion of these individuals were recaptured outside the study area, confirming that the RKC may conduct long-distance migrations. The remaining individuals of RKC responded quickly to changes in ambient water temperature, seeking deeper and colder waters masses when the temperature in shallower waters increased. Several individuals showed nearly identical spatio-temporal distributions, which supports earlier observations of crab aggregations. Our data indicates that the area utilization of the RKC is affected by trade-offs between biotic and abiotic factors, in which sub-optimal water temperatures may be tolerated provided appropriate access to food. Thus, our findings suggest that the current knowledge of RKC seasonal migration patterns may need to be revised, which in turn will have implications for managers and the fishing industry. This study demonstrates the high potential of telemetry studies to yield new, high-resolution data and knowledge of species' ecology.